2020
DOI: 10.1155/2020/3164056
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Epidemiological Survey of Work-Related Musculoskeletal Disorders and Analysis of Its Influencing Factors among Coal Mine Workers in Xinjiang

Abstract: This study is to investigate the prevalence of work-related musculoskeletal disorders (MSDs) and the influencing factors among coal mine workers employed in on-site operations. The job burnout scale and MSD scale were implemented to investigate a random sample of 1,500 coal mine workers working in on-site operations in Xinjiang, China. In total, 1,325 valid questionnaires were collected, with a recovery rate of 88.33% (1,325/1,500). The rate of job burnout was 90%, of which 39.8% were categorized as mild burno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
3
7
2
Order By: Relevance
“…It was found that significant work under conditions of cold or temperature variations had positive contributions to the prevalence of WMSDs in most body parts. This is consistent with previous reports of mining [ 25 ] and cold store work [ 26 ]. The results indicated that musculoskeletal symptoms are more frequent in cold exposure than in normal temperature work.…”
Section: Discussionsupporting
confidence: 94%
“…It was found that significant work under conditions of cold or temperature variations had positive contributions to the prevalence of WMSDs in most body parts. This is consistent with previous reports of mining [ 25 ] and cold store work [ 26 ]. The results indicated that musculoskeletal symptoms are more frequent in cold exposure than in normal temperature work.…”
Section: Discussionsupporting
confidence: 94%
“…Associated with work-related musculoskeletal disorders in miners were participants with secondary education, no breaks during a typical working day, and operating machinery that produces whole-body vibration. findings confirm previous observations from multiple studies that suggest miners are associated with an increased prevalence of WMSD (10); (11); (12). The reported prevalence in this study is much higher when compared with that reported in previous studies conducted in China among construction workers (57.9%) (13), in Pakistan among construction workers (52%) (14), in Democratic republic of Congo among gold mine workers (61.2%) (5), and in India among surface miners (44.2%) (15).…”
Section: Discussionsupporting
confidence: 92%
“…Compared with other shift miners in the two shift group have a longer working hours,so they have higher degree of musculoskeletal fatigue and cannot get sufficient rest. As a result, muscle fatigue gradually accumulates, leading to the occurrence of MSDs [ 51 ]. Coal miners have the highest prevalence of MSDs.…”
Section: Discussionmentioning
confidence: 99%